Clinical Outcome of Intravenous Immunoglobulin in the treatment of Guillain Barre Syndrome in a Nepalese Tertiary Centre - Ojha, Rajeev; Karn, Ragesh (Nepalese Medical Journal, 2019)
Introduction: Intravenous Immunoglobulin is an approved therapy for Guillain Barre Syndrome. Our objective is to understand the management and outcome in Guillain Barre Syndrome patients treated with Immunoglobulin. Materials and Methods: All consecutive patients were retrospectively evaluated in the study were of age ≥16 years and were being admitted in the department of Neurology of Tribhuvan University Teaching Hospital, Kathmandu, Nepal from 2016 March to 2017 February. Results: A total of 46 patients were included, mean age= 36.5±16.2 years, range = 16years to 80 years. Thirty-two patients (70%) were axonal variant, acute motor axonal neuropathy is more common (18 patients). Intravenous immunoglobulin was used in 23 patients (50%), 17 of them were axonal variant and 6 were demyelinating. Guillain Barre Syndrome patients with bilateral facial weakness (70% vs 30%; p<0.05) were likely to receive immunoglobulin therapy. Patients with immunoglobulin were found to have higher ODSS at Nadir (9.3±1.8 vs 6.9±1.9; p <0.001) and discharge than patients without immunoglobulin treatment (6.2±1.7 vs 5.0±1.6; p=0.001). At Nadir, Patients with immunoglobulin were found to have higher Guillain Barre Syndrome disability score (4.1±0.7 vs 3.2±0.9; p<0.095). In immunoglobulin group, Axonal variants were found to have higher ODSS score (9.6±1.9 vs 8.2±0.9, p=0.027) and Guillain Barre Syndrome disability score (4.2±0.7 vs 3.5±0.5; p=0.019) at nadir than demyelinating group. Conclusions: Intravenous Immunoglobulin is easier to administer and is safe with fewer adverse effects. Although expensive, it is an effective treatment option in a resource-limited center. Axonal variants are clinically severe and likely to be need of Intravenous Immunoglobulin therapy.